PERAN PERGERAKAN MAHASISWA ISLAM INDONESIA (PMII) KOTA SALATIGA DALAM MENYEBARKAN NILAI-NILAI ISLAM NUSANTARA - Ahmad Wasi'; Muna Erawati (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2019)
This research is aimed at finding out: 1) PMII roles of Salatiga in 2017 in order to spread values of Islam Nusantara; 2) the inhibing and supporting factors faced by PMII of Salatiga in spreading the values. To get the data needed in this study, the researcher used qualitative descriptive methodology by using library and field research. This result of this study showed that spreading the values of Islam Nusantara consists of two roles named formal and informal roles. While the supporting factors in spreading the values of Islam Nusantara are: a) the number of seniors of PMII became lecturers at the two campuses;b) the large number of Islamic boarding schools around two campuses that have a commissariat of PMII; c) many members who become santri, are affiliated with campus internal organizations; and d) the majority of members are NU backgrounds. while the inhibiting factors are as follows: the number of campuses in Salatiga is relatively few , there are only two Islamic universities around Salatiga, the number of members and administrators are unequal, and the lack of capacity of the committee, and they lulled by the big name of NU.